2011
DOI: 10.1111/j.1475-6773.2011.01335.x
|View full text |Cite
|
Sign up to set email alerts
|

Costs of Addressing Heroin Addiction inMalaysia and 32 Comparable Countries Worldwide

Abstract: Objective. Develop and apply new costing methodologies to estimate costs of opioid dependence treatment in countries worldwide. Data Sources/Study Setting. Micro-costing methodology developed and data collected during randomized controlled trial (RCT) involving 126 patients ( July 2003-May 2005 in Malaysia. Gross-costing methodology developed to estimate costs of treatment replication in 32 countries with data collected from publicly available sources. Study Design. Fixed, variable, and societal cost component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…This is consistent with results from prior micro-costing analyses of education and behavioral interventions in other substance use populations (e.g., university and middle school students, emergency department patients), which have generally shown low program costs [23], [40], [41], [42], [43]. Our estimates also compare favorably to findings from a recent micro-costing study on opioid dependence treatment in Malaysia combining naltrexone and buprenorphine with manual-guided counseling [24].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is consistent with results from prior micro-costing analyses of education and behavioral interventions in other substance use populations (e.g., university and middle school students, emergency department patients), which have generally shown low program costs [23], [40], [41], [42], [43]. Our estimates also compare favorably to findings from a recent micro-costing study on opioid dependence treatment in Malaysia combining naltrexone and buprenorphine with manual-guided counseling [24].…”
Section: Discussionsupporting
confidence: 89%
“…The costs assessed in this study were consistent with recommendations by the U.S. Panel on Cost Effectiveness in Health and Medicine to use standardized techniques [13] and methodologies developed and employed in previous studies by members of our research team [23], [24], [25]. The micro-costing method entailed a three-step approach that identified, estimated and valued resource utilization for each intervention arm.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…6,7 This is particularly the case in Puerto Rico, a US territory. A 2008 household survey conducted to examine the need for drug treatment in the island's general population revealed that 78% of the persons meeting diagnostic criteria for drug dependence received health care through the publicly funded health care sector.…”
Section: Introductionmentioning
confidence: 93%
“…20 More recent research has demonstrated the cost-effectiveness of BUP treatment for heroin dependence and compared the cost of treating heroin addiction with buprenorphine in Malaysia and 32 other countries. 21 …”
Section: Malaysiamentioning
confidence: 99%